Le projet professionnel et personnel des étudiants, assise de leur professionnalisation ? - Daniel Bart; Michel Fournet (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
This article analyzes projects carried out by students taking part in a professional academic master programme. It focuses on how the students “translate” the programme into “learning strategies” for their professional development. Analysing students’ answers in a questionnaire enables to get a better understanding of the genesis of their projects and to bring out various issues regarding three main components : 1) elements of purpose, 2) conceptions regarding programmes and 3) skills acquired through experience. This article also shows in which ways these projects support a wide range of student commitments and learning strategies. To conclude, we emphasise that this research requires a pedagogical approach that takes into consideration the projects’ design and their contribution towards professional development.